METTL3/m6A/IFIT2 regulates proliferation, invasion and immunity in esophageal squamous cell carcinoma - Ge, Fangfang; Li, Zhenyu; Hu, Jiaru; Pu, Youguang; Zhao, Fangfang; Kong, Lingsuo (Frontiers in Pharmacology, 2022)
Tumorigenesis, development, and treatment all rely heavily on epigenetic regulation. The most common chemical modification of mRNA, known as m6A, is essential for controlling the stability, splicing, and translation of mRNA. METTL3 is an important methylation enzyme, and we found that METTL3 has a significant proliferative effect in the tissues and cells of esophageal squamous cell carcinoma (ESCC). The term was highly regulated, and overexpression of METTL3 facilitated the development of ESCC. Through transcriptome sequencing, IFIT2 was identified as a downstream target of METTL3. The findings revealed that METTL3 regulates IFIT2 and thus influences malignant biological behaviors such as proliferation, migration, and invasion of ESCC, as well as the immune microenvironment of tumors.